Trade customs unions and their impact on trade - Chudobova, Claire; Štěrbová, Ludmila, 1957-; Halík, Jaroslav, 1961-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This paper concentrates on customs unions and their impact on trade. We have chosen two trading blocs that we believe are interesting cases: MERCOSUR and EU. Throughout the thesis, we will look more closely into how those customs unions were created and on what objectives were they based upon. Furthermore, to understand more precisely the complexity of those trading blocs, we will talk about their historical development and economical situation. As well as their attitudes towards international trade. For the latter, we will look into each trading blocs trade policies, institutions and presence in international trade. In order to understand better the differencies in trading blocs, a comaprison of those two will be later on discussed together with their impacts.
Vedoucí práce: Ludmila Štěrbová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses